Therapeutic use of spontaneous medicinal flora from an extreme environment (dune cordon) in Djelfa region, Algeria - Benalia Yabrir; Mostefa Touati; Benzian Adli; Elhadi Bezini; Mounir Ghafoul; Saoussane Khalifa; Brahim Guit (GarVal Editorial Ltda., 2018)
Context: In some extreme environments such as dune cordon in the region of Djelfa, the ability of species to adapt to extreme conditions, especially climatic stresses, appears to be highly developed. Notwithstanding this importance from an ecophysiological point of view, the plant genetic resources of the Algerian steppe are very little known and especially poorly valued. Aims: To inventorying the spontaneous species in an extreme "dune cordon" environment of the Algerian steppe and to collect information on the ancestral know-how of the local populations in terms of therapeutic use of these species. Methods: Foremost, a herbarium has been made which includes all species inventoried in dune cordon, then an ethnobotanical survey materialized by a direct questionnaire was conducted with different actors involved in the field of medicinal plants. It concerns the traditional use of these species. Results: Seventeen plants (20%) of the listed plant species have been recognized and identified as medicinal species. These plants belong to 13 families of which the Lamiaceae family is the most represented, followed by Asteraceae and Poaceae. Several diseases are treated by these species by local populations, some have a definite therapeutic use while others are used in the treatment of several diseases. The most incriminated pathologies concern rheumatism, diabetes, dental pain, fever and renal function. Leaves are most used with decoction as the most used mode. Conclusions: Results of the study showed that dune cordon contains a wide variety of spontaneous plants, which have a beneficial interest. It also indicated the link between natural resources and humans and the therapeutic use of these species for profit by local population. The rich ethno-pharmacological knowledge of this population must be preserved and valued. A phytochemical screening and biological investigation are needed to test this ancestral know-how.